Outcome of Wide Local Excision and V-Y Plasty for Axillary Hidradenitis Suppurativa - Islam, Sardar Rezaul; Emon, Mohammad Hanif; Sarkar, Shah Alam; Paul, Debabroto (British Journal of Healthcare and Medical Research, 2023)
Background: Hidradenitis suppurativa (HS) is a chronic, relapsing, inflammatory skin condition that greatly affects patients’ quality of life. The patient with HS presents with inflammation of hair follicles in the apocrine gland-bearing regions (armpits, genital area, groin, inframammary region, perianal region and buttocks). It can be associated with fistulating sinus, scarring and abscesses formation. We present our experience of treating axillary HS by wide local excision and V-Y plasty advancement flap. Methods: A retrospective analysis reviewed 23 patients, out of which 21 were female and 3 were male. Age range was 17 to 31 years. All were having axillary HS. Five patients were having bilateral disease. 19 patients had one stage V-Y plasty. Only 4 patients had severe infections and multiple abscess formation at the time of Wide excision. They were managed by 2 stage procedure. Wide excision first and secondary flap coverage after 10 days. They were followed for 1 year for recurrence of the disease. Results: Average post operative hospital stay was 6 days. 3 patients had wound infections which did not require any secondary procedure.21 patients showed no recurrence after surgery. 2 patients had minor recurrence at the periphery of the axilla of the flap coverage. They did not require further surgical procedure. There was no contracture. All had full range of movement of the shoulder. Conclusion: Wide local excision is the best surgical treatment for advanced HS. V-Y plasty advancement flap from the inner aspect of the arm is a very easy procedure to cover axillary skin loss. The procedure has a very low recurrence. The mobility of the shoulder joint is unaffected.